2015
DOI: 10.1016/j.molmet.2015.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular regulation of urea cycle function by the liver glucocorticoid receptor

Abstract: ObjectiveOne of the major side effects of glucocorticoid (GC) treatment is lean tissue wasting, indicating a prominent role in systemic amino acid metabolism. In order to uncover a novel aspect of GCs and their intracellular-receptor, the glucocorticoid receptor (GR), on metabolic control, we conducted amino acid and acylcarnitine profiling in human and mouse models of GC/GR gain- and loss-of-function.MethodsBlood serum and tissue metabolite levels were determined in Human Addison's disease (AD) patients as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…In fetal rat, cortisol has been shown to stimulate liver ARG1 after an intraperitoneal injection (Husson & Vaillant, ). In patients with Addison's disease, which exhibit a loss of function of the liver glucocorticoid receptor (GR) after acute withdrawal from treatment and in mouse models of systemic and liver‐specific GR loss‐of‐function (AVV‐miR‐GR), an increased ratio arginine/(ornithine+citrulline) was observed (Okun et al., ). Furthermore, liver mRNA expression profiling identified ARG1 as a target of GR (Okun et al., ).…”
Section: Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fetal rat, cortisol has been shown to stimulate liver ARG1 after an intraperitoneal injection (Husson & Vaillant, ). In patients with Addison's disease, which exhibit a loss of function of the liver glucocorticoid receptor (GR) after acute withdrawal from treatment and in mouse models of systemic and liver‐specific GR loss‐of‐function (AVV‐miR‐GR), an increased ratio arginine/(ornithine+citrulline) was observed (Okun et al., ). Furthermore, liver mRNA expression profiling identified ARG1 as a target of GR (Okun et al., ).…”
Section: Variantsmentioning
confidence: 99%
“…In patients with Addison's disease, which exhibit a loss of function of the liver glucocorticoid receptor (GR) after acute withdrawal from treatment and in mouse models of systemic and liver‐specific GR loss‐of‐function (AVV‐miR‐GR), an increased ratio arginine/(ornithine+citrulline) was observed (Okun et al., ). Furthermore, liver mRNA expression profiling identified ARG1 as a target of GR (Okun et al., ). This study concluded that liver glucocorticoid/GR controls the urea cycle function by transcriptional regulation of ARG1 expression (Okun et al., ).…”
Section: Variantsmentioning
confidence: 99%
“…Glucocorticoids are known to have direct effects on skeletal muscle to induce muscle atrophy, despite intact liver GR signaling 24,25 . Therefore, although the liver GR was not a critical component 43 , our results demonstrate that blocking the previously observed 65 increase in liver ALT activity could confer an abrogation in the muscle atrophy upon synthetic glucocorticoid treatment. The lack of effects of the liver GR action might be explained by the partial action of liver-GR silencing on the upregulation of liver ALT expression ( Fig.…”
Section: Discussionmentioning
confidence: 43%
“…The muscle atrophy, and related weakness, in T2D could be reversed by a silencing of the upregulation of liver alanine catabolism, an intriguing result. Such a result is not unfounded however, as some prior studies have linked liver metabolic control with systemic protein turnover and skeletal muscle phenotype 43,44 . Similar to our studies in mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced availability of ATP can thus limit formation of carbamoyl phosphate and its subsequent reaction with ornithine, thereby leading to accumulation of ornithine (p=0.01) and reduced levels of citrulline and arginine (trend), as observed in our data. Further, elevated arginase expression is shown to be associated with increased inflammatory cytokines and GC activity 46 , which could further lead to a lower urea cycle flux, reduced arginine levels and subsequent nitric oxide production. This is also supported by a significant positive association between cortisol suppression and ornithine (ρ=0.223, p=0.004, q=0.015) and a trend of causal association between hs-CRP and arginine ( =- 0.05, p=0.05, q=0.145, τ 2 =0.211).…”
Section: Resultsmentioning
confidence: 99%